Functional genomic tools for emerging model species. (December 2022) - Gudmunds, Erik; Wheat, Christopher W.; Khila, Abderrahman; Husby, Arild
Abstract : Most studies in the field of ecology and evolution aiming to connect genotype to phenotype rarely validate identified loci using functional tools. Recent developments in RNA interference (RNAi) and clustered regularly interspaced palindromic repeats (CRISPR)-Cas genome editing have dramatically increased the feasibility of functional validation. However, these methods come with specific challenges when applied to emerging model organisms, including limited spatial control of gene silencing, low knock-in efficiencies, and low throughput of functional validation. Moreover, many functional studies to date do not recapitulate ecologically relevant variation, and this limits their scope for deeper insights into evolutionary processes. We therefore argue that increased use of gene editing by allelic replacement through homology-directed repair (HDR) would greatly benefit the field of ecology and evolution. Highlights: Understanding the molecular mechanisms underlying phenotypic evolution is a central goal in evolutionary biology. Unfortunately, causal associations between candidate loci and the phenotype are rarely established because the majority of associations are never validated with functional tools. We describe the latest developments in the use of functional tools, particularly RNAi and clustered regularly interspaced palindromic repeats (CRISPR)-Cas, to establish causal links between genotype and phenotype, and discuss some methodological challenges when applying these tools that are unique to emerging model organisms. Specifically, we highlight a significant issue in that current functional studies in ecology and evolutionary biology to date rarely recapitulate ecologically relevant variation, and we suggest that gene editing in emerging model species should make more use of the HDR pathway to obtain relevant functional insights and thereby a deeper understanding of the genetic basis of traits.